Arrhythmia classification using local Holder exponents and support vector machine - Joshi, Aniruddha; Rajshekhar; Chandran, S.; Phadke, S.; Jayaraman, Valadi K.; Kulkarni, B. D. (1st International Conference on Pattern Recognition and Machine Intelligence, 2005)
We propose a novel hybrid Holder-SVM detection algorithm for arrhythmia classification. The Holder exponents are computed efficiently using the wavelet transform modulus maxima (WTMM) method. The hybrid system performance is evaluated using the benchmark MIT-BIH arrhythmia database. The implemented model classifies 160 of Normal sinus rhythm, 25 of Ventricular bigeminy, 155 of Atrial fibrillation and 146 of Nodal (A-V junctional) rhythm with 96.94% accuracy. The distinct scaling properties of different types of heart rhythms may be of clinical importance.

Facile method for the synthesis of Co-core Au-shell nanohybrid - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal Of Chemistry, 2014)
Heterostructured Co-Au core-shell nanoparticles have been synthesized by reducing AuCl4- ions on cobalt nanoparticles after a minor but effective modification of cobalt surface by an amine. The core shell morphology is emphatically confirmed by thorough investigation through UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and transmission electron microscopic analysis (TEM). The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirms the surface modification of Co nanoparticles and the interactions involved between the ligands and the core and shell metals at various steps of the synthetic process. The magnetic properties confirm the material to be superparamagnetic in nature.

Microscopic hydration properties of the a beta(1-42) peptide monomer and the globular protein ubiquitin: a comparative molecular dynamics study - Jose, Jaya C.; Khatua, Prabir; Bansal, Nupur; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Journal of Physical Chemistry B, 2014)
Atomistic molecular dynamics simulations of eight selected conformations of a disordered protein amyloid beta (1-42) (A beta), and a globular protein, ubiquitin(UBQ), have been carried out in aqueous media at 310 K. Detailed analyses were carried out to compare the microscopic properties of water molecules present in the hydration layers of these systems. It is notices that irrespective of the conformational heterogeneity among the A beta monomers, water molecules hydrating UBQ. Importantly, the conformational heterogeneity of the A beta monomers has been found to affect the translational and rotational motions of hydration water molecules in a nonuniform manner. Detailed investigation of the timescale of hydrogen bond relaxations at the surface and their energetics revealed the possibility of heterogeneous confinement around different A beta conformations. The distribution of water density fluctuation around A beta conformations are broader compared density fluctuation among the A beta monomers suggests that the structural propensities could affect the peptides effective surface hydrophobicity.

Multifaceted core-shell nanoparticles: superparamagnetism and biocompatibility - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Ahir, Manisha; Adhikary, Arghya; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2015)
NicoreAgshell nanoparticles were synthesized by redox transmetallation reaction. Reduction potential match was encouraging to attempt the synthesis of the NicoreAushell system too. However, it could be achieved only after an effective surface modification on the Ni-core. Thorough characterization (UV-Vis spectroscopy, fluorescence spectroscopy, XRD, XPS, FTIR, TEM, and EDX) proved the necessity of surface modification and the success of synthesis of both types of core-shell structures. The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirmed the surface modification of Ni nanoparticles and the interactions involved between the ligands and metals (in the core and/or the shell) at various steps of the synthetic process. Even after the formation of the noble metal shell, the magnetic core was found to retain its superparamagnetic nature. In addition, the Au-shell protected the core from aerial oxidation and decreased toxicity as compared to pristine Ni nanoparticles as observed by MTT assay on normal cells (PBMCs).

Conformational features of the Aβ42 peptide monomer and its interaction with the surrounding solvent - Khatua, Prabir; Jose, Jaya C.; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Physical Chemistry Chemical Physics, 2016)

Multiple functionalities of Ni nanoparticles embedded in carboxymethyl guar gum polymer: catalytic activity and superparamagnetism - Sardar, Debasmita; Sengupta, Manideepa; Bordoloi, Ankur; Ahmed, Md. A.; Neogi, S. K.; Bandyopadhyay, Sanjoy; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (Applied Surface Science, 2017)
Composites comprising of metallic nanoparticles in polymer matrices have allured significant importance due to multifunctionalities. Here a simple protocol has been described to embed Ni nanoparticles in carboxymethyl guar gum (CMGG) polymer. The composite formation helps in the stabilization of Ni nanoparticles which are otherwise prone towards aerial oxidation. Further the nanoparticles retain their superparamagnetic nature and catalytic capacity. Ni-Polymer composite catalyses the reduction of 4-Nitrophenol to 4-Aminophenol very efficiently in presence of NaBH4, attaining a complete conversion under some experimental conditions. Ni-Polymer composite is well characterized using UV–vis spectroscopy, FTIR, XPS, powder XRD, TGA, SEM and TEM. A detailed magnetic measurement using superconducting quantum interference device-vibrating sample magnetometer (SQUID-VSM) reveals superparamagnetic behaviour of the composite.